Introduction. Cities and urban policy - Krau, Ingrid (Raumforschung und Raumordnung | Spatial Research and Planning, 2008)
Issue 4/2007 of this journal was dedicated to EU structural policy and the European structural funds, including the impacts of distribution. This current issue addresses European cities as compact spheres of economic activity, and their strategic importance for the implementation of a European policy of accelerated growth, also with a critical view on a mere aiming for the goals of the Lisbon Strategy. This involves analysis and discussion of various current approaches at national level and of the development trends of integration-based urban policy in the field of tension between the Lisbon Strategy and territorial cohesion. In addition to historical developments and local strategies, focus is also placed on the analysis and (further) development of models of urban governance with their idealised notion of a local community of responsibility; European reality does, however, to a greater of lesser extent diverge from this ideal.
Keywords: Urban Development Policy; Europe; Lisbon Strategy; Territorial Cohesion; Governance